Geometrical-based characterisation of complex ti-6al-4v parts fabricated by selective electron beam melting - Kok, Yihong (2016)
In an additive manufactured metallic part, distinct and different microstructure and mechanical properties may exist on different areas due to differences in shape and location. Two parts, one with straight-finned structure and one with curvefinned structure, were fabricated by selective electron beam melting method using prealloyed Ti-6Al-4V powder. Microstructural characterization of these two parts that have varying fin thickness and shape were carried out in order to investigate the synthetically influence of build geometry and in-fill hatching strategy on selective electron beam melting. It was found that the β-spacing is larger in the curve-finned structure, leading to a lower micro-hardness as compared to the straight-finned structure. It suggests a slower cooling rate in the curve-finned structure due to the differences in build geometry and infill hatching strategy.